Impacts of system of rice intensification farming on marginal land / Wan ‘Alia Husna Wan Abdullah - Wan ‘Alia Husna, Wan Abdullah (2017)
Soil and water quality plays a vital role in crop yields. However, with degradation of soil and water quality due to extreme weather, excessive chemical inputs and lack of agricultural land, paddy production in Malaysia remained stagnant over the past decade. Shifting agriculture on marginal (infertile) land is currently one of the options to mitigate this problem. However, a good farming management is crucial in conducting any development on marginal land for agriculture. Hence, this study focuses on assessing soil and impounded water quality for marginal soil under the system of rice intensification (SRI) farming method. The soil suitability of this land for crop growth was found poor due to weathering process and deteriorating of soil fertility. Therefore, this study aimed at improving the quality of marginal land through the environ-friendly system of rice intensification (SRI) method. SRI is an agroecological method that helps to increase the productivity of paddy farming by changing the management aspects of crops, soil, irrigated water and nutrients, which are hypothetically able to provide better crops. Soil and impounded water quality under five farming stages during SRI method (land preparation, transplanting, water circulation, fertiliser management and harvest) at 12 experimental paddy plots were analysed. Overall qualities of the soil and impounded water by SRI method have been significantly improved (Kruskal-Wallis test at probability level = 0.05). Moreover, limit of the optimum nutrient requirements was complied. When SRI performance was compared to the secondary data of conventional farming method, SRI was found improving its impounded water quality. Therefore, it can be concluded that SRI method can be used to improve the marginal soil for paddy plantation.